Social-psychological factors of the formation of professional special characteristics in a leader person - Baxram Jumanazarov (Zien Journals, 2024)
Today's pedagogue is required by society to be managed by a person who embodies all-round leadership competence and has a new way of managing employees. In this article, there are opinions about the students who are placed in front of the modern leader today.
Keywords: pedagogue-leader; educational system; modern education